2021
DOI: 10.1089/dna.2020.6447
|View full text |Cite
|
Sign up to set email alerts
|

FCER1GandPTGS2Serve as Potential Diagnostic Biomarkers of Acute Myocardial Infarction Based on Integrated Bioinformatics Analyses

Abstract: This study aimed to explore the potential diagnostic biomarkers and mechanisms underlying acute myocardial infarction (AMI). We downloaded four datasets (GSE19339, GSE48060, GSE66360, and GSE97320) from the Gene Expression Omnibus database and combined them as an integrated dataset. A total of 153 differentially expressed genes (DEGs) were analyzed by the linear models for microarray analysis (LIMMA) package. Weighted gene co-expression network analysis was used to screen for the significant gene modules. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…PTGS2, prostaglandin-endoperoxide synthase 2, also known as COX2, is an enzyme involved in prostaglandin synthesis, which is associated with cardiovascular disease risk. Its expression was increased in MI ( Ge et al, 2019 ; Xiao et al, 2021 ). It was reported that PTGS2 genetic variant, may be important risk factors for the development of cardiovascular disease events ( Lee et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTGS2, prostaglandin-endoperoxide synthase 2, also known as COX2, is an enzyme involved in prostaglandin synthesis, which is associated with cardiovascular disease risk. Its expression was increased in MI ( Ge et al, 2019 ; Xiao et al, 2021 ). It was reported that PTGS2 genetic variant, may be important risk factors for the development of cardiovascular disease events ( Lee et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that miRNA-26b alleviates the inflammatory response and remodeling of the heart in MI by targeting PTGS2 ( Ge et al, 2019 ). Recently, PTGS2 was reported that can serve as potential diagnostic biomarkers of AMI ( Xiao et al, 2021 ). So, PTGS2 was an important gene in MI.…”
Section: Discussionmentioning
confidence: 99%
“…PLA2G2A [61], CCL23 [62], CD53 [63], TREML4 [64], TREM2 [65], CD180 [66], HPSE (heparanase) [67], CELA2A [68], TNFRSF4 [69], AMBP (alpha-1-microglobulin/bikunin precursor) [70], SOX18 [71], PANX2 [72], RSPO2 [73], COMP (cartilage oligomeric matrix protein) [74], ASGR1 [75] and NOXA1 [76] are involved in progression of atherosclerosis. A previous study reported that S100A9 [77], ADORA3 [78], IL1R2 [79], FPR1 [80], CCL20 [81], CD163 [82], S100A8 [83], TLR2 [84], HAS2 [85], PTX3 [86], TIMP4 [87], AREG (amphiregulin) [88], LBP (lipopolysaccharide binding protein) [89], IL18R1 [90], ALOX5AP [91], RETN (resistin) [92], F13A1 [93], FPR2 [94], SAA1 [95], FLT3 [96], AQP4 [97], FCER1G [98], CCL18 [99], HP (haptoglobin) [100], CDK1 [101], SLC7A11 [102], CFTR (CF transmembrane conductance regulator) [103], F8 [104], STC1[44], IL18RAP [90], TIMP3 [105], PDE4D [106], CYP4A11 [107], SCN10A [108], APOB (apolipoprotein B) [109], ACE (angiotensin I converting enzyme) [110], PENK (proenkephalin) [111], HSPB6 [112], TLR9 [113], EGR1 [114], CACNG8 [115], FOXD3 [116], DBH (dopamine beta-hydroxylase) [117], FOXP3 [118], GLP1R [119], IL34 [120], CCN1 [121], ADRA2A [122], BGN (biglycan) [123], NOS2 [124], AGRN (agrin) [125], DRD1 [126], GNB3 [127], EGR2 [128], MDK (midkine) [129], NOTCH3 [130], AZIN2 [131], NOTCH1 [132], LOX...…”
Section: Discussionmentioning
confidence: 99%
“…7, CFTR, CDK1, RPS13, RPS15A, RPS27, NOTCH1, MRPL12, NOS2, CCDC85B and ATN1 achieved an AUC value of >0.88, demonstrating NOXA1 [76] are involved in progression of atherosclerosis. A previous study reported that S100A9 [77], ADORA3 [78], IL1R2 [79], FPR1 [80], CCL20 [ [96], AQP4 [97], FCER1G [98], CCL18 [99], HP (haptoglobin) [100], CDK1 [101], SLC7A11 [102], CFTR (CF transmembrane conductance regulator) [103], F8 [104], STC1 [44], IL18RAP [90], TIMP3 [105], PDE4D [106], CYP4A11 [107], SCN10A [108], APOB (apolipoprotein B) [109], ACE (angiotensin I converting enzyme) [110], PENK (proenkephalin) [111], HSPB6 [112], TLR9 [113], EGR1 [114], CACNG8 [115], FOXD3 [116], DBH (dopamine beta-hydroxylase) [117], FOXP3 [118] [189], MAOA (monoamine oxidase A) [190], BMPR1B (bone morphogenetic protein receptor type 1B) [191], FGF7 [192], CALCRL (calcitonin receptor like receptor) [193], MARK3 [194], ADH1B [195], AMH (anti-Mullerian hormone) [196], RET (ret proto-oncogene) [197], IGF2 [198], SLC6A9 [199], NPPA (natriuretic peptide A) [200], SCT (secretin) [201], DCX (doublecortin) [202...…”
Section: Validation Of Hub Genes By Receiver Operating Characteristic Curve (Roc) Analysismentioning
confidence: 99%
“…It can describe the pattern of gene association and explore the interactions between gene expression profiles and potential functional relationships. It is increasingly used to identify hub genes associated with cardiovascular diseases ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%